L’espace frontalier, région en construction - Estelle Evrard (Belgeo)
Supranational regionalisation – as initiated on the rubble of the Cold War – increases the complexity and multiplicity of a border’s functions. Novel institutional and functional developments structure border areas, making their analysis complicated. This paper aims to analyse this situation in terms of the structuring of border areas. It postulates that supranational regionalisation, such as the European integration process, contributes to the emergence of regionalisation processes at an infranational and transnational level. This paper presents a theoretical framework for a qualitative analysis, allowing cross-border cooperation to be read from the angle of the construction of a region. A “region” is considered a spatio-temporal structure resulting from the evolution of society. This conceptualisation raises the question to what extent actual cross-border cooperation goes beyond the initial intentions of institutional actors to create a progressive autonomy. Two factors contribute to this process: the institutionalisation of the border area as an autonomous entity stimulating the development of the region under construction; the territorialisation of cooperation, i.e. the projection of a common strategy followed by an appropriation of the area.